Meaning Equivalence and Shift of Noun Phrases in Bilingual Children’s Literature; Indonesian into English Translation - Sari Puspita Dewi (Journal Polingua: Scientific Journal of Linguistics, Literature and Language Education, 2018)
The study aims at describing the equivalence and shift occuring in translating noun phrases. Library research was applied to this study. The data were taken from two bilingual picture books entitled Princess Mui Zee written by Firma Sutan, Princess Barruna written by Shinta Handini and their translation into Indonesian by Asih Gandana as the translator. The result of the study shows that the meaning equivalence often occurs in formal correspondence. Then, the study also finds the structure shift existed in 15 NPs of both stories; the class shift occured in 3 NPs of both series; the unit shift happened in 1 NP of both series and the intra-system shift occured in 2 NPs.